Monitor to Protect: The Proliferation of Bio-Connected Devices in Supply Chains - Paché, Gilles (Technium Social Sciences Journal, 2024)
The use of bio-connected devices (BCDs) in medicine and perishable logistics marks a significant advancement in product traceability and flow security. These devices, equipped with heat-sensitive biosensors, allow for real-time monitoring of storage and delivery conditions. This ensures that medicines, particularly vaccines, and perishable goods are kept within proper temperature ranges, preventing deterioration. Additionally, BCDs play a crucial role in combating counterfeiting through transparent traceability systems, often enhanced with blockchain technology, which guarantees product authenticity throughout the supply chain. However, the adoption of these innovative technologies faces several barriers, including high initial costs, data security concerns, and the need for adequate technical infrastructure. Despite these challenges, BCDs have substantial potential to transform the food and pharmaceutical industries by boosting operational efficiency and ensuring product safety.